Multiple Myeloma of the Thyroid Cartilage - Peter Kalina; Jeffrey B. Rykken (Case Reports in Hematology)
A 60-year-old male presented with hoarseness. His past medical history was remarkable for a plasmacytoma of the left maxillary sinus having been resected without systemic evidence of plasma cell myeloma (PCM), also known as multiple myeloma (MM), at the time. This maxillary sinus disease recurred and was treated with radiation. Workup for PCM was conducted. Treatment included melphalan and autologous stem cell transplant. Because of the therapeutic and prognostic implications, a Plasma cell neoplasm (PCN) in a neck mass must be carefully evaluated by clinical and pathological criteria in order to distinguish plasmacytoma from PCM. PCN involvement of the thyroid cartilage is very rare, with only 5 previously reported cases.